PERAN GANDA BURUH PEREMPUAN DI PERUSAHAAN PT DELTA PASIFIC INDOTUNA KOTA BITUNG PROVINSI SULAWESI UTARA - Fikram Djurumudi (Universitas Sam Ratulangi, 2023)
Humans will not be separated from the demands of the role that must be lived in the development of their lives, as well as women workers. Women workers have the role of wives in the family, namely as companions of husbands and successors of offspring. While her role as a mother is to care, guide, and educate her children to grow up. The development and progress of the industry today where the involvement of women in the production sector is common which causes not a few women to enter the industrial sector. Women working in the industrial sector will be faced with two demanding roles, namely as housewives and as breadwinners. Most of those who work in the fishery company PT Delta Pacific Indotuna Bitung City are female workers. Women work as laborers because previously they were people who did not have a job and also mothers who only took care of the household without getting wages so that there was a desire from them (women) to work as laborers in the company because they saw people who worked in the company their economic life experienced changes / increases in meeting family needs. The utilization of the income they earn for various needs in the household and the needs of their children which indirectly they have helped ease the economic burden borne by the husband as the head of the household. As women who have a workload, of course, women must be able to divide time between family and work. They use the time before going to work to take care of their household first, after finishing taking care of the household, then they prepare to work. Keywords: dual role, woman, factory worker